2018
DOI: 10.1038/s41598-018-23966-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Design and Fabrication of Biomimetic 3D Scaffolds: Unique Architectures of Extracellular Matrices for Enhanced Adipogenesis and Soft Tissue Reconstruction

Abstract: The higher rate of soft tissue impairment due to lumpectomy or other trauma greatly requires the restoration of the irreversibly lost subcutaneous adipose tissues. The nanofibers fabricated by conventional electrospinning provide only a superficial porous structure due to its sheet like 2D structure and thereby hinder the cell infiltration and differentiation throughout the scaffolds. Thus we developed a novel electrospun 3D membrane using the zwitterionic poly (carboxybetaine-co-methyl methacrylate) co-polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Associated with increasing global population mobility, aging, accidents, war and displacement, trauma and organ/tissue damages such as, organ degeneration, bone fracture and maxillofacial complications have been still rampant [ 2 ]. In addition to the physical trauma and functional impairment, such damages do have critical psychosocial and emotional implications [ 3 , 4 ]. Transplantation using donated organs has been practiced in different settings in addition to available pharmacological and supportive treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Associated with increasing global population mobility, aging, accidents, war and displacement, trauma and organ/tissue damages such as, organ degeneration, bone fracture and maxillofacial complications have been still rampant [ 2 ]. In addition to the physical trauma and functional impairment, such damages do have critical psychosocial and emotional implications [ 3 , 4 ]. Transplantation using donated organs has been practiced in different settings in addition to available pharmacological and supportive treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a cost-effective technique for synthesizing polymeric fibers with diameters ranging from a few nanometers to tens of microns. Nanofibers electrospun with conventional benchtop electrospinners have found application in textiles [1,2], energy harvesting and storage [3,4,5,6], tissue engineering [7,8,9,10], packaging of pharmaceuticals [11] and wound healing [12,13,14,15] among others [16,17,18,19,20]. Although these traditional electrospinners can produce copious quantities of nanofibers, their large size and stationary design limit their utility in many key applications such as point-of-need nanofiber deposition (e.g., direct application of nanofibers to wound dressings in the clinic) and consumer end-user scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in this review, fiber alignment, micropatterning, and controlled porosity of nanofibrous mats have all been found to have significant effect on cellular behavior, inducing cell attachment, migration and differentiation. Extensive research has been conducted on exploring morphological cues provided by 2D electrospun mats, and only recently fibrous 3D scaffolds have been proposed to closely mimic the ECM structure (Cai et al, 2013 ; Lee et al, 2014 ; Cho et al, 2016 ; Hwang et al, 2018 ; Unnithan et al, 2018 ). The studies conducted so far have demonstrated that a fine tuning of the 3D porosity of the electrospun scaffolds is crucial to promote cell infiltration.…”
Section: Discussionmentioning
confidence: 99%